Circumcision to prevent HIV and other sexually transmitted infections in men who have sex with men: a systematic review and meta-analysis of global data. Issue 4 (April 2019) - Yuan, Tanwei; Fitzpatrick, Thomas; Ko, Nai-Ying; Cai, Yong; Chen, Yingqing; Zhao, Jin; Li, Linghua; Xu, Junjie; Gu, Jing; Li, Jinghua; Hao, Chun; Yang, Zhengrong; et al.
Summary: Background: Men who have sex with men (MSM) are disproportionately affected by HIV and other sexually transmitted infections (STIs) worldwide. Previous reviews investigating the role of circumcision in preventing HIV and other STIs among MSM were inconclusive. Many new studies have emerged in the past decade. To inform global prevention strategies for HIV and other STIs among MSM, we reviewed all available evidence on the associations between circumcision and HIV and other STIs among MSM. Methods: In this systematic review and meta-analysis, we searched PubMed, Web of Science, BioMed Central, Scopus, ResearchGate, Cochrane Library, Embase, PsycINFO, Google Scholar, and websites of international HIV and STI conferences for studies published before March 8, 2018. Interventional or observational studies containing original quantitative data describing associations between circumcision and incident or prevalent infection of HIV and other STIs among MSM were included. Studies were excluded if MSM could not be distinguished from men who have sex with women only. We calculated pooled odds ratios (ORs) and their 95% CIs using random-effect models. We assessed risk of bias using the Newcastle-Ottawa scale. Findings: We identified 62 observational studies including 119 248 MSM. Circumcision was associated with 23% reduced odds of HIV infection among MSM overall (OR 0·77, 95% CI 0·67–0·89; number of estimates [k]=45; heterogeneity I 2 =77%). Circumcision was protective against HIV infection among MSM in countries of low and middle income (0·58, 0·41–0·83; k=23; I 2 =77%) but not among MSM in high-income countries (0·99, 0·90–1·09; k=20; I 2 =40%). Circumcision was associated with reduced odds of herpes simplex virus (HSV) infection among MSM overall (0·84, 0·75–0·95; k=5; I 2 =0%) and penile human papillomavirus (HPV) infection among HIV-infected MSM (0·71, 0·51–0·99; k=3; I 2 =0%). Interpretation: We found evidence that circumcision is likely to protect MSM from HIV infection, particularly in countries of low and middle income. Circumcision might also protect MSM from HSV and penile HPV infection. MSM should be included in campaigns promoting circumcision among men in countries of low and middle income. In view of the substantial proportion of MSM in countries of low and middle income who also have sex with women, well designed longitudinal studies differentiating MSM only and bisexual men are needed to clarify the effect of circumcision on male-to-male transmission of HIV and other STIs. Funding: National Natural Science Foundation of China, National Science and Technology Major Project of China, Australian National Health and Medical Research Council Early Career Fellowship, Sanming Project of Medicine in Shenzhen, National Institutes of Health, Mega Projects of National Science Research for the 13th Five-Year Plan, Doris Duke Charitable Foundation.